The Philosophical Trilogy for The Development of Islamic Educational Management - Achmad, Achmad; Fitria, Lailatul (TATHO: International Journal of Islamic Thought and Sciences, 2024)
This research aims to formulate a theoretical framework for Islamic education management based on the integration of ontology, epistemology and axiology as a deep philosophical foundation. Islamic education management theory often adopts a secular approach that prioritizes material efficiency without considering spiritual and moral values in the Islamic context. Therefore, this research proposes a theocentric approach that emphasizes the importance of monotheism in ontology, the integration of revelation and empirical knowledge in epistemology, and the application of maslahah values in axiology. By using a descriptive-analytic qualitative approach through literature study, this research examines how these three dimensions can be integrated with each other to produce Islamic education management theory that is relevant to contemporary challenges. The research results show that the integration of ontology, epistemology and axiology in Islamic education management not only provides practical solutions, but also enriches the spiritual, moral and social dimensions in the management of educational institutions. It is hoped that the resulting theory can be a new contribution to the Islamic education management literature with an applicable approach but still maintaining the authenticity of Islamic values.